The Effect of STEAM-Based Project Learning on Junior High School Students’ Collaboration Skills - Shafira, Shafira; Saehana, Sahrul; Paramitha, Ielda (Journal of Innovative Physics Education Research, 2025)
This study aims to determine the effect of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach on the collaboration skills of junior high school students. The study employed a true experimental method with a Posttest-Only Control Group Design. The research population consisted of all 148 seventh-grade students of SMP Negeri 18 Palu in the 2023/2024 academic year. Sampling was conducted using a purposive sampling technique based on specific considerations from the physics teachers at SMP Negeri 18 Palu. Class VII A was designated as the experimental group that implemented the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach within the Project Based Learning (PjBL) model, while Class VII B served as the control group using the scientific approach in PjBL. The instrument used was a collaboration skills observation sheet consisting of four assessment indicators. The results of data analysis using the Independent Sample t-test revealed a significant difference between the experimental and control groups, with a Sig. (2-tailed) value of 0.004 < 0.05. These findings indicate that the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach has a significant effect on students’ collaboration skills. Therefore, the implementation of STEAM-based learning is an effective alternative for enhancing students’ collaboration skills in science learning at the junior high school level. Furthermore, these findings confirm that the STEAM approach is not only relevant for integrating multiple disciplines but also contributes significantly to the development of 21st-century collaboration skills, thereby strengthening and extending previous studies that primarily focused on improving students’ learning outcomes and creativity.